2020
DOI: 10.1111/coa.13520
|View full text |Cite
|
Sign up to set email alerts
|

Elective neck dissection for salvage total laryngectomy: A systematic review, meta‐analysis and “decision‐to‐treat” approach

Abstract: IntroductionThe authors provide an updated, systematic and comprehensive summary of the literature concerning management of the N0 neck in patients for whom primary irradiation for squamous cell carcinoma of the larynx has been unsuccessful and salvage surgery in the form of total laryngectomy (TL) advocated.MethodsBibliographic databases MEDLINE, Cochrane, PubMed and Embase were searched from inception to April 2019, with no language restrictions. The Preferred Reporting Items for Systematic Reviews and Meta‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…In previously published reports, the rate of positive lymph nodes in all salvage laryngeal cases inclusive of cN0 and cN+ patients at the time of salvage has a broad range from 0% to 46%. 7-10 In one of the largest single-institution studies of neck dissection outcomes in laryngeal salvage, Birkeland et al 27 reported a 24% rate of identifying positive lymph nodes in patients undergoing salvage surgery, compared to 26% in the present study. Rates of occult metastasis for cN0 patients at the time of salvage surgery in individual studies range from 0% to 31%.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations
“…In previously published reports, the rate of positive lymph nodes in all salvage laryngeal cases inclusive of cN0 and cN+ patients at the time of salvage has a broad range from 0% to 46%. 7-10 In one of the largest single-institution studies of neck dissection outcomes in laryngeal salvage, Birkeland et al 27 reported a 24% rate of identifying positive lymph nodes in patients undergoing salvage surgery, compared to 26% in the present study. Rates of occult metastasis for cN0 patients at the time of salvage surgery in individual studies range from 0% to 31%.…”
Section: Discussionmentioning
confidence: 41%
“…There is considerable variability in reported nodal metastasis rates in patients undergoing neck dissection (ND) during salvage laryngeal surgery, ranging from 0% to 46% amongst all patients and from 0% to 31% in cN0 patients undergoing elective ND. 7-10 Many authors have shown low yield of positive lymph nodes, higher complication rates, and ultimately no improvement in regional control or survival outcomes. 10-14 Still, some authors who have shown a higher rate of nodal metastasis or survival benefit advocate for neck dissection in the salvage setting either routinely or in selected cases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, several previous retrospective studies showed no significant influence of elective neck dissection (END) on survival in advanced laryngeal cancers (Ketterer et al 2020;Shi et al 2019;Kennedy et al 2017;Djordjevic et al 2016;Canis et al 2012). For salvage TL cases, END is not generally recommended, because, although it reduces the rate of regional recurrence, it does not provide a survival benefit as stated in a recent meta-analysis (Davies-Husband et al 2020).…”
Section: Discussionmentioning
confidence: 98%